EFFECTS OF MULTIPLE INTELLIGENCE TEACHING STRATEGY ON STUDENTS’ ACADEMIC ACHIEVEMENT AND ATTITUDES TOWARDS CHEMISTRY IN JALINGO EDUCATION ZONE OF TARABA STATE, NIGERIA - JACK, Gladys; JAPHET, Judith (Ilorin Journal of Education, 2023)
The study investigated the effects of Multiple Intelligence Teaching Strategy on Students’ academic achievement and attitudes towards Chemistry in Jalingo Education Zone of Taraba State, Nigeria. Quasi-experimental design, involving the non-equivalent control group design and was used for the study. The study used an intact class made up of 183 Chemistry students of Senior School Two (99 males and 84 females) drawn from two public science oriented senior secondary schools. Multiple Intelligence Teaching Strategy Chemistry Achievement Test (MITSCAT) and Students Attitudes towards Chemistry Inventory (SATCI) were the instruments for data collection. Data collected were analysed using Mean and Standard Deviation to answer the research questions and Analysis of Covariance to test the hypotheses at 0.05 level of significance. The findings revealed that there is a significant difference between the mean-achievement scores of the students taught Chemistry using Multiple Intelligence Teaching Strategy (MITS) and those students taught Chemistry using Conventional Lecture Teaching Method. The findings also showed that there is no significant difference in attitude scores between the two groups; male and female students mean-achievement scores; and male and female students attitude scores taught Chemistry using MITS and conventional lecture teaching method. It is therefore concluded that to enhance higher achievement and attitude of students in Chemistry, MITS should be adopted. It is recommended amongst others that Chemistry teachers be exposed to MITS since it is learners-centred, gender-friendly, and enhances students’ attitudes and achievement in Chemistry